1926
DOI: 10.1098/rspb.1926.0034
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the onset of rigor mortis

Abstract: These observations on rigor mortis were made from time to time on cats and rabbits dying after large doses of insulin, on rabbits dying as a result of prolonged thyroid feeding, and on spinal cats to which large doses of insulin had been administered to study the carbohydrate metabolism of the muscles. Rabbits which have received large doses of insulin, and which, as a result, have had periods of convulsions and collapse, may either die very quickly or may survive for long periods. The exact cause of the death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1932
1932
1999
1999

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Many factors such as exercise, cause of death, temperature and nourishment affect the onset or progress of rigor mortis of the whole body [9,33,[42][43][44]. Concerning rigor mortis in each joint, of course we have to consider that it is not just one muscle that moves a joint.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many factors such as exercise, cause of death, temperature and nourishment affect the onset or progress of rigor mortis of the whole body [9,33,[42][43][44]. Concerning rigor mortis in each joint, of course we have to consider that it is not just one muscle that moves a joint.…”
Section: Discussionmentioning
confidence: 98%
“…Glycogen is the most important substrate for ATP formation by glycolysis in postmortem muscles [3,9,33] and the final product of glycolysis is lactic acid. Postmortem glycogenolysis in a single muscle has been studied in detail [34,35] but never in different muscles.…”
Section: Discussionmentioning
confidence: 99%
“…None of the normal frogs of Ochoa (30) and of Gemmill (10) had muscles that contracted anaerobically without glycolysis, although some of those treated with insulin did so. These three workers and Hoet and Marks (15) consider that a necessary and sufficient condition for anaerobic contraction without glycolysis is depletion of the muscle stores of carbohydrate. Gemmill (10) implied that the capacity of the muscle to do work anaerobically is directly proportional to the carbohydrate level, the important carbohydrate being glycogen.…”
Section: Experiments With Fatigued Musclesmentioning
confidence: 99%
“…If sartorii and gastrocnemii of R. temporaria and R. esculenta have low carbohydrate reserves, they can contract aerobically on sources of energy only partly carbohydrate (30,10). When mammalian muscles are rendered low in glycogen by the use of insulin or thyroid, rigor mortis in them is not accompanied by glycogenolysis or by lactate production (15). Olmsted and his colleagues (31,32) were the first to use insulin convulsions for rendering muscles of R. pipiens and R. catesbiana nearly free of glycogen; muscles so prepared contracted anaerobically without glycogenolysis or lactate production.…”
mentioning
confidence: 99%
“…Although much of the early work on rigor mortis attributed carcass stiffening after death to lactic acid production and the resultant drop in pH, Hoet and Marks (1926) suggested that this was not the fundamental reason for carcass stiffening. They concluded that lactic acid would not cause rigor by itself but that it would affect the amount of shortening and tension produced.…”
Section: Post-mortem Musclementioning
confidence: 99%